Legal Politics Dynamics in the Era of Digital Democracy: Ensuring Free and Fair Elections in Indonesia’s 2024–2029 Electoral Cycle - Ryan Gunawan (Nusantara: Journal of Law and Islamic Law, 2025)
This study examines the dynamics of legal politics in Indonesia’s digital democracy era, with a focus on ensuring free and fair elections. Utilizing a normative juridical approach, data were gathered through statutory analysis of laws, implementing regulations, and judicial decisions, complemented by a conceptual review of legal-political theory, digital democracy, and political party power. In-depth interviews with election organizers and expert validation of instruments provided additional qualitative insights. The analysis reveals that digitalization has transformed political parties’ strategies, shifting power toward those adept at leveraging digital platforms and algorithms to mobilize support. While digital tools have expanded political participation and transparency, they also pose risks of algorithmic manipulation, disinformation, and elitist control of digital spaces. The study identifies institutional weaknesses in party discipline, ideological coherence, and internal democracy that undermine compliance with democratic norms. It highlights the prevalence of pragmatic and opportunistic elite behavior, which leads to selective issue framing and erosion of public trust. To address these challenges, the research proposes strengthening legal frameworks governing digital campaign practices, enhancing party education on democratic values, and improving mechanisms for transparency and accountability in both online and offline political processes. By reinforcing internal party democracy and promoting normative adherence to constitutional mandates, Indonesia can harness digital democracy to uphold electoral integrity and realize the constitutional principle of popular sovereignty.